STUDI BEBAN FATIK TERHADAP KAPASITAS LENTUR BALOK BETON BERTULANG PERKUATAN GLASS FIBER REINFORCED POLYMER SHEET - Fatriady MR (Journal Techno Entrepreneur Acta, 2016)
The useful life of reinforced concrete structural elements could mean that the structural elements of reinforced concrete is not able to withstand the repeated load. In this regard, conducted research that aims to understand the behavior of reinforced concrete flexural loading fatigue and effects receives tired and reinforcements Sheet Glass Fiber Reinforced Polymer (GFRP-S). Methods to set boundaries or controls in the calculation of the capacity of the test beam and its impact on behavior and reinforcement in the beam test obtained in a number of references. This study makes a test beam with a full-scale model with a size of 300 x 500 x 6000 mm. Number of test blocks are provided each with 4 pieces of reinforced concrete. Tests conducted on the technique of static loading on 3 pieces of test beams A 1, B 1 and B 2 and the fatigue loading on the first specimens of B 2 with 1:25 Hz cycle frequency. The results showed that the effect of fatigue on concrete receiving sufficient load capacity and a big influence on the behavior of concrete. Concrete receiving static load is able to accept a maximum load of 470 kN while the concrete receiving the fatigue load is able to accept the fatigue load minimum 75 kN and 260 kN maximum endures to 1,300,000 cycles with a greater deflection behavior. Observations on the beam construction of static and fatigue loading test showed retrofitting of GFRP-S is able to increase the capacity of the test beam in the receiving load. Capacity test on the beam reinforcement GFRP has not mencapai ultimate theoretical capacity, so it needs further study regarding pengaruh cracking and melting before retrofitting GFRP rebars. Analysis of fatigue in structures is essential for the achievement of the design life of the structure and the salvation of mankind